2019
DOI: 10.1101/19002097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute hepatitis C infection among adults with HIV in the Netherlands: a capture-recapture analysis

Abstract: Background: Reliable surveillance systems are essential to assess the national response to eliminating hepatitis C virus (HCV), in the context of the global strategy towards eliminating viral hepatitis. Aim: We aimed to assess the completeness of the two national registries of acute HCV infection in people with HIV, and estimated the number of acute HCV infections among adults with HIV in the Netherlands. Methods: For 2003-2016, cases of HCV infection and reinfection among adults with a positive or unknown H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our study included data from a large cohort involving nearly all PWH in care in the Netherlands. Furthermore, a recent capture-recapture analysis showed that between 2013 and 2016 99% of acute HCV infections of HIVpositive individuals registered in the Dutch National Registry for Notifiable Diseases were captured in the ATHENA cohort [25]. Thus, we believe that the coverage of data offered by the ATHENA cohort is sufficient to understand issues related to DAA treatment access at a wide-reaching level.…”
Section: Barriers To Direct-acting Antiviral Treatment Uptakementioning
confidence: 92%
“…Our study included data from a large cohort involving nearly all PWH in care in the Netherlands. Furthermore, a recent capture-recapture analysis showed that between 2013 and 2016 99% of acute HCV infections of HIVpositive individuals registered in the Dutch National Registry for Notifiable Diseases were captured in the ATHENA cohort [25]. Thus, we believe that the coverage of data offered by the ATHENA cohort is sufficient to understand issues related to DAA treatment access at a wide-reaching level.…”
Section: Barriers To Direct-acting Antiviral Treatment Uptakementioning
confidence: 92%